ASSESSMENT OF AWARENESS OF RECOMMEN-DATIONS FOR PREVENTION OF BACTERIAL ENDOCARDITIS AMONG A GROUP OF 136 IRANIAN DENTAL AND MEDICAL STUDENTS - M. R. Zarei; N. Navabie G. Chamani (Acta Medica Iranica, 2008)
Bacterial endocarditis is a serious disease that could occur after invasive dental procedures. Despite a large number of papers written about the knowledge of prevention of bacterial endocarditis among health care workers in western countries, little is known about awareness of this subject among practitioners and students in other countries. The purpose of the present study was to assess the knowledge of recommendations for prevention of bacterial endocarditis among a group of Iranian dental and medical students. A multiple choice test that included 15 questions about bacterial endocarditis and antibiotic prophylaxis was developed. The questionnaires were distributed to 136 dental and medical students who had passed a theoretical course about bacterial endocarditis successfully in the past. Success was defined as correct answers to at least 8 of the 15 questions. Of 136 students participating in this study, 34 (25%) passed the test successfully. The pass-rate of dental students (38%) was significantly higher than that of medical students (13.5%) (P < 0.05). The mean mark of dental and medical students was 6.74 ± 2.28 and 4.81 ± 2.1, respectively (P < 0.05). No significant difference in success rates or mean marks found according to sex or age in the present study. The results of the present study demonstrate an important lack of knowledge regarding prevention of bacterial endocarditis among a group of Iranian dental and medical students and the need for improved education in this field.